Brain Tumor MRI Image Segmentation Using Deep Learning Techniques - Chaki, Jyotismita (Elsevier Science & Technology, 2021)
Brain Tumor MRI Image Segmentation Using Deep Learning Techniques offers a description of deep learning approaches used for the segmentation of brain tumors.The book demonstrates core concepts of deep learning algorithms by using diagrams, data tables and examples to illustrate brain tumor segmentation.